Monitoring Education Policy through Quality Assurance Agency - Khambali, Khambali; Zakiah, Qiqi Yuliati; Supiana, Supiana (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
The purpose of writing this scientific paper is to understand the concept and practice of monitoring education policies through the Quality Assurance Agency implemented at the Islamic University of Bandung. The method used in writing this scientific paper is an analytical descriptive study with a qualitative approach. Data was obtained by conducting documentation studies and interviews. The results found indicate that monitoring of education at the Bandung Islamic University is marked by the existence of a number of policies and activities of the Bandung Islamic University Quality Assurance Agency. Quality assurance is intended to maintain and guarantee the level of quality on an ongoing basis aspects which include input, process, and output.